1997
DOI: 10.1128/aem.63.2.679-686.1997
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Transfer between Spatially Separated Donor and Recipient Bacteria in Earthworm-Containing Soil Microcosms

Abstract: Most gene transfer studies have been performed with relatively homogeneous soil systems in the absence of soil macrobiota, including invertebrates. In this study we examined the influence of earthworm activity (burrowing, casting, and feeding) on transfer of plasmid pJP4 between spatially separated donor (Alcaligenes eutrophus) and recipient (Pseudomonas fluorescens) bacteria in nonsterile soil columns. A model system was designed such that the activity of earthworms would act to mediate cell contact and gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Earthworm cocoon fluid has been found to elicit an immune response against several bacterial species, which indicates that earthworms may be able to control the cocoon microbiota (30). This is also suggested by Daane et al (7), who reported consistent recovery of Ralstonia eutropha (formerly Alcaligenes eutrophus) from Aporrectodea trapezoides cocoons formed in inoculated soil. In addition, Zachmann and Molina (32) reported that Escherichia coli could not be recovered from cocoons formed in microcosms inoculated with this bacterium.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Earthworm cocoon fluid has been found to elicit an immune response against several bacterial species, which indicates that earthworms may be able to control the cocoon microbiota (30). This is also suggested by Daane et al (7), who reported consistent recovery of Ralstonia eutropha (formerly Alcaligenes eutrophus) from Aporrectodea trapezoides cocoons formed in inoculated soil. In addition, Zachmann and Molina (32) reported that Escherichia coli could not be recovered from cocoons formed in microcosms inoculated with this bacterium.…”
supporting
confidence: 83%
“…R. eutropha JMP222N is a nalidixic acid-resistant mutant of JMP222, a streptomycin-resistant, cured derivative of R. eutropha JMP134(pJP4) (21). R. eutropha JMP222N containing pJP4 was obtained by patch mating as previously described (7). Plasmid pJP4 is an IncP, broad-host-range plasmid containing genes for mercury resistance and 2,4-D and 2,4-DCP degradation (21).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If, however, soil conditions do not sustain signi¢cant cell growth, then conjugation will only occur if the inoculation process itself leads to contact between the two populations, e.g. if cell concentrations are high, unless mechanisms such as bulk £ow, movement of soil and animals, and growth of plant roots and fungal hyphae promote dispersal of cells [26,27]. Previous studies aimed at testing models of gene transfer in the soil have eliminated spatial e¡ects by utilisation of high cell concentrations and high matric potentials that enhanced mobility [28].…”
Section: Discussionmentioning
confidence: 99%